Sistem Monitoring Agen Pada Xavier Marks Realty Surabaya - Robertus Bagas; Emmy Wahyuningtyas (Informatics Engineering Department-UWKS, 2020)
Xavier Marks Realty is a company engaged in property marketing. The company runs, several obstacles prevent the leadership to make decisions. The availability of information needed by the leadership is very slow because each agent still has to enter sales closing data manually through the admin not directly. The purpose of this research is to create an effective monitoring system, as well as to accelerate the availability of information for leaders. The results of this study can be in the form of an agent monitoring system that can update property sales data directly through an agent without filling in manually and inputted through the admin. Earnings reports from agents and companies will be directly received by the leadership, thus cutting down the admin's performance. The system can display sales developments so that each agent can improve its performance and the leader can monitor directly the agent.